Brief review on experimental and computational techniques for characterization of cellular metals - Duarte, Isabel (2020)
The paper presents a brief review of the main experimental and numerical techniques and standards to investigate and quantify the structural, mechanical, thermal, and acoustic properties of cellular metals. The potential of non-destructive techniques, such as X-ray computed tomography and infrared thermography are also presented.